PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN MESIN CUCI MEREK POLYTRON DI MEDAN - Eka Umi Kalsum; Sri Liniarti; Rizky Surya Andhayani Nasution (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This article highlight of product quality and services on customer satisfaction using Polytron brand washing machines in Medan, North Sumatra. Theories used in this study include product quality theory, service theory and consumer satisfaction theory. The population in this study were 78 users of Polytron brand washing machines in Medan City, North Sumatra. The data analysis model used is multiple linear regression analysis. The research method uses a descriptive quantitative approach that is supported by a survey, and is explanatory. The results of the study by testing the t-test hypothesis showed that product quality had a positive and significant effect on consumer satisfaction using Polytron brand washing machines in Medan. Service has a positive and significant impact on consumer satisfaction using Polytron brand washing machines in Medan. The results of the F test indicate that the quality of products and services has a positive and significant effect on consumer satisfaction using Polytron brand washing machines in Medan. The value of the coefficient of determination (R2) of product and service quality is able to explain the consumer satisfaction variable of 95.5% and the remaining 4.5% is influenced by other variables not examined in this study such as price, promotion, location and so on.